PENGARUH ANGGARAN FUNGSI PENDIDIKAN TERHADAP ANGKA PARTISIPASI SEKOLAH, ANGKA PARTISIPASI KASAR, DAN ANGKA PARTISIPASI MURNI - Dahiri (Pusat Kajian Anggaran, 2023)
The education function budget over the period 2005–2022 has continued to increase. However, the school enrollment rate has decreased with age. Therefore, this paper aims to analyze the effect of the education function budget on the school enrollment rate, gross enrollment rate, and net enrollment rate. The research method in this study uses a quantitative research approach with a regression model. The results showed that first, the education function budget has a positive and significant effect on APS, APK, and APM. Second, APK SM/MA and APK PT are still below the target. Third, the APM disparity at the SD/MI level does not show inequality in access to education between men and women. Even at the levels of junior secondary school, senior secondary school, and tertiary level (19–24 years old), female APM is higher than male. Therefore, the government's efforts to improve education development include increasing scholarships for children from poor families and prioritizing budget support for improving facilities and infrastructure at the primary and vocational levels for sanitation.